2003
DOI: 10.1128/aac.47.8.2538-2544.2003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Daptomycin Bactericidal Activity and Membrane Depolarization in Staphylococcus aureus

Abstract: The objective of this study was to further elucidate the role of membrane potential in the mechanism of action of daptomycin, a novel lipopeptide antibiotic. Membrane depolarization was measured by both fluorimetric and flow cytometric assays. Adding daptomycin (5 g/ml) to Staphylococcus aureus gradually dissipated membrane potential. In both assays, cell viability was reduced by >99% and membrane potential was reduced by >90% within 30 min of adding daptomycin. Cell viability decreased in parallel with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
524
2
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 595 publications
(550 citation statements)
references
References 26 publications
(31 reference statements)
19
524
2
5
Order By: Relevance
“…58 Similarly, Silverman et al employed a K + -sensitive fluorescent probe to demonstrate that 5 µg/ml daptomycin can trigger K + release from S. aureus suspended in Hepes buffer (pH 7.2). 73 K + release is accompanied by a collapse of membrane potential, as evidenced by the release of the membrane-permeant cation tetraphenylphosphonium; in contrast, the transmembrane pH gradient remains unaffected, as shown by the unaltered cellular accumulation of acetylsalicylic acid (ASA), a weak acid organic acid whose protonated form equilibrates across the membrane. 74 Daptomycin inhibits the cellular uptake of amino acids by active transport, which depends on the membrane potential.…”
Section: Membrane Depolarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Similarly, Silverman et al employed a K + -sensitive fluorescent probe to demonstrate that 5 µg/ml daptomycin can trigger K + release from S. aureus suspended in Hepes buffer (pH 7.2). 73 K + release is accompanied by a collapse of membrane potential, as evidenced by the release of the membrane-permeant cation tetraphenylphosphonium; in contrast, the transmembrane pH gradient remains unaffected, as shown by the unaltered cellular accumulation of acetylsalicylic acid (ASA), a weak acid organic acid whose protonated form equilibrates across the membrane. 74 Daptomycin inhibits the cellular uptake of amino acids by active transport, which depends on the membrane potential.…”
Section: Membrane Depolarizationmentioning
confidence: 99%
“…79 From the above observations, the question naturally arises whether membrane permeabilization also controls the time course of bactericidal action. While this question was answered in the affirmative by Silverman et al, 73 Hobbs et al maintain that the loss of cell viability precedes that of biosynthetic capacity. However, their reported kinetics of cell killing and biosynthetic collapse differ only by some minutes.…”
Section: Depletion Of Substrates and Metabolic Energymentioning
confidence: 99%
See 1 more Smart Citation
“…8 Our previous studies revealed that PRG-A exerted rapid bactericidal activity against staphylococci and enterococci via a mechanism that involved disruption of the membrane integrity of the target cells, 9 a mode of action distinct from that of daptomycin. 9,10 During the process of optimization of PRG-A production, we discovered new active components PRG-B, -C and -D (Figure 1) in the culture broth of the PRG-A-producing strain Amycolatopsis sp. ML1-hF4.…”
mentioning
confidence: 99%
“…5 Daptomycin is a clinical antibiotic that disrupts the membrane potential by inserting into the membrane, creating Ca 2+ -dependent pores, and releasing intracellular ions. 8 Disrupting the transmembrane potential using daptomycin may also mislocalize membrane-associated proteins that are involved in essential cellular processes, ultimately leading to membrane permeability and cell death. 9 We recently discovered 2-((3-(3,6-dichloro-9H-carbazol-9-yl)-2-hydroxypropyl)amino)-2-(hydroxymethyl) propane-1,3-diol (DCAP, 1, Figure 1) in a high-throughput screen designed to identify small molecule inhibitors of MipZ, an ATPase that regulates the location of the division site in Caulobacter crescentus.…”
mentioning
confidence: 99%